Modelling And Simulation Of Cationic Dye Adsorption Using Modified Metal-Organic Framework-5 (MOF-5) - Wan Mazlan, Wan Hamizan (Universiti Sains Malaysia, 2021)
Modelling and simulation of cationic dye adsorption by using modified Metal-Organic Framework-5 was studied. Mathematical model was developed based on a two-resistance model which included external mass transfer coefficient and pore diffusion coefficient that controls the mass transfer process in batch adsorption. MATLAB R2020b software was used to estimate the mass transfer parameters which are mass transfer coefficient (kf) and pore diffusion coefficient (Dp) by matching the simulation data with the experimental data from literature. The value of kf and Dp were estimated to be 66.8 m/s and 2.1514×10-7 m2/s respectively. By using the estimated parameters, simulation results showed that the model provided good correlation with the experimental data based on different initial concentrations. The estimated parameters were used to study the adsorption of Methylene Blue (MB) by using modified MOF-5under different factors such as modification of MOF-5, initial dye concentration, temperature and the mass of adsorbent. It was concluded that the dye removal efficiency was higher for modified MOF-5 (H6P2W18O62/MOF-5). Not only that, the lower initial dye concentration, higher temperature and higher adsorbent mass also result in higher dye removal efficiency.